Keadilan Perpajakan, Sistem Perpajakan, Diskriminasi Perpajakan, Teknologi, Informasi Perpajakan, dan Tax Evasion - Rahmayanti, Putu Eka; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2023)
The research aims to determine the influence of tax fairness, the tax system, tax discrimination, technology and tax information on taxpayers on tax evasion. This research was conducted at the East Denpasar Pratama Tax Service Office. The population in this study are taxpayers who carry out business activities and are registered with KPP Pratama Denpasar Timur. The sampling technique uses a purposive sampling method. The number of samples in this research was 100 taxpayers who carried out business activities and were registered and the number of samples used in this research was determined based on the approach. The analysis technique used is Multiple Linear Regression. The results of the analysis show that tax fairness, the tax system, technology and tax information for taxpayers have a significant negative effect on tax evasion, while tax discrimination has a significant positive effect on tax evasion. Keywords : justice; systems; discrimination; TI; tax evasion